"Captain Filastine" and the Trappings of Success. Issue 1 (2nd January 2022) - Elia, Nada
Abstract: Many Arab Americans cheered Lieutenant Filastine Srour's promotion to the rank of captain in the New York City Police Department as if this constituted a collective victory for Palestinians. But one person rising up in a notoriously racist institution does not end their community's criminalization. Nor is individual advancement by a woman a feminist accomplishment, as feminism aspires to dismantle oppressive systems, not succeed in them.